OPPORTUNITIES FOR SUSTAINABILITY OF SMALL BUSINESS ENTERPRISES ON THE BASIS OF IMPROVING THE BUSINESS ENVIRONMENT IN UZBEKISTAN - Aripov Oybek Abdullayevich; Nematova Charosxon Rasuljon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article addresses some of the issues, such as the opportunities for small businesses to sustain themselves by improving the business environment in Uzbekistan.